Unleashing Potential: The Role of Merdeka Curriculum in Transforming English Education - Fitriani, Fitriani (Trigin Institute, 2025)
This study investigated the implementation of the Merdeka Curriculum in 10th-grade English classes in Musi Banyuasin, focusing on its impact on teaching techniques, assignment workload, and curriculum adaptability. Using a qualitative approach, data were collected through classroom observations and semi-structured interviews with English teachers. Findings indicated that interactive teaching methods, such as group discussions and Q&A sessions, enhanced student engagement, aligning with the curriculum’s objectives. However, teachers reported that the high volume of assignments led to “assignment fatigue” among students, impacting motivation and learning effectiveness. Additionally, teachers faced challenges in adapting lessons to the curriculum’s flexible framework, highlighting a need for support in curriculum adaptation. The study concluded that while the Merdeka Curriculum shows promise in fostering active, student-centered learning, adjustments in assignment volume and enhanced teacher training are essential for optimal implementation. These insights contribute to understanding the practical applications of the Merdeka Curriculum and suggest areas for improvement in English language education.